Research Study That Is Oriented On Social Issues As The Impact Of Globalization - Bayu Bambang Nurfauzi; Deni Tata Kusuma; Husen Ali Badri; Mohammad Erihadiana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Globalization cannot be underestimated by its arrival, because it will definitely have good and bad impacts on people's lives. On the other hand, a handful of people are eagerly awaiting the impact of globalization because they want as many of the world's treasures as possible to be piled up and exhibited. It is hoped that with Islamic education, Muslims can progress in a better direction and not be left behind by the times. The method used is a qualitative method of library approach. So that with the progress of globalization raises a common thread from every research conducted by researchers, namely bringing up solutions in the era of globalization. The results of the study can be concluded that scientific development, educational attainment goals, and other problems cannot be solved with sciences that have stopped since ancient times, what should be taught in Islamic education apart from religious knowledge is also taught about scientific technology, culture, philosophy and others that according to the times. These sciences need to be collaborated in modern Islamic education to answer emerging problems that are increasingly being actualized.